2010
DOI: 10.1142/s0219061310000924
|View full text |Cite
|
Sign up to set email alerts
|

On the Complexity of the Successivity Relation in Computable Linear Orderings

Abstract: Abstract. In this paper, we solve a long-standing open question (see, e.g., Downey [6, §7] and Downey and Moses [11]), about the spectrum of the successivity relation on a computable linear ordering. We show that if a computable linear ordering L has infinitely many successivities, then the spectrum of the successivity relation is closed upwards in the computably enumerable Turing degrees. To do this, we use a new method of constructing ∆ 0 3 -isomorphisms, which has already found other applications such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…The key idea of our proof is similar to the proof technique in Downey, Lempp, and G. Wu [6], who prove that for any computable linear ordering with infinitely many successivities, there is a computable isomorphic copy in which the successivity relation has degree 0'. The idea there was not to try to produce a A^-isomorphism by effectively approximating it by finite partial isomorphisms, but to define finite parts of a Aj-isomorphism along the true path of an infinite-injury priority argument on a tree of strategies.…”
Section: Main Theorem Let Si Be An Infinite N-like Computable Linearmentioning
confidence: 97%
“…The key idea of our proof is similar to the proof technique in Downey, Lempp, and G. Wu [6], who prove that for any computable linear ordering with infinitely many successivities, there is a computable isomorphic copy in which the successivity relation has degree 0'. The idea there was not to try to produce a A^-isomorphism by effectively approximating it by finite partial isomorphisms, but to define finite parts of a Aj-isomorphism along the true path of an infinite-injury priority argument on a tree of strategies.…”
Section: Main Theorem Let Si Be An Infinite N-like Computable Linearmentioning
confidence: 97%
“…Our first example shows that, for a fixed computably enumerable Turing degree c, the relations T and I can both be intrinsically of degree c. This term was used in [2], in which Downey and Moses showed that the relation of adjacency in a computable linear order can be intrinsically of degree 0 ′ . Subsequently, Downey, Lempp, and Wu showed in [1] that the only degrees c for which the adjacency relation can be intrinsically of degree c are c = 0 ′ and (if the adjacency relation is finite) c = 0. Therefore Theorem 2 distinguishes the situation for transcendence and for independence in fields from that of adjacency in linear orders.…”
Section: Examples Of Degree Spectramentioning
confidence: 99%
“…Let us first start with the errors in the proof of our Main Theorem in [2] in the case of a linear order A in which any infinite interval is η-like but not strongly η-like. Specifically, in the description of the full W a -strategy in Sec.…”
mentioning
confidence: 99%
“…With these two changes, Lemmas 3.2(4)(b) and 3.2(5)(c) are now correct as stated. Now let us turn to the missing case to establish our Main Theorem in [2], namely, the case when the linear order A is η-like but has no infinite strongly η-like interval nor a limit point of successivities handledà la Chubb et al It is not hard to check that any such order must contain an infinite interval of the form…”
mentioning
confidence: 99%
See 1 more Smart Citation